Modified high-titanium heavy slag micropowder and preparation method thereof

By adding composite activation modification additives to the high-titanium heavy slag micro powder and grinding, the problems of low activity and high water absorption when used in concrete are solved, which significantly improves the working performance and durability of concrete and promotes the high added value utilization of waste slag.

CN119661107APending Publication Date: 2025-03-21CHINA CONSTR WEST CONSTR SOUTHWEST CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411890063.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

When high-titanium heavy slag powder is used in concrete, the active ingredients content is low and the water absorption is high, resulting in an increase in concrete viscosity, large admixture dosage, poor working performance, and components such as TiO2 are difficult to disperse evenly, reducing the density and durability of concrete.

Method used

Modified high-titanium heavy slag micro powder, whose raw materials include high-titanium heavy slag waste slag and composite activation modification additives, reduce water absorption and enhance gelling activity through the grinding process. Complex activation modifiers include dispersants, water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, which are used to improve the hydrophobicity and gelling properties of the micropowder.

Benefits of technology

It effectively improves the water absorption rate and gelling activity of high-titanium heavy slag micro powder, improves the working performance and durability of concrete, promotes the recycling and utilization of high-titanium heavy slag waste slag, and has a simple preparation method and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200435480000061
    Figure BDA0005200435480000061
Patent Text Reader

Abstract

The invention discloses modified high-titanium heavy slag micro-powder, raw materials of the modified high-titanium heavy slag micro-powder comprise high-titanium heavy slag waste residues and an activating and modifying additive, and the compound activating and modifying additive comprises the following components in parts by weight: 15-20 parts of a dispersing agent, 35-40 parts of water, 30-35 parts of normal propyl alcohol, 6-10 parts of sodium methoxide, 0.5-2 parts of 1, 2-bis (triethoxysilyl) ethane and 7-12 parts of isobutyltriethoxysilane. The modified high-titanium heavy slag micro-powder is prepared by taking the high-titanium heavy slag waste residues and the composite activated modified additive as main raw materials and combining a grinding process, so that the activity and the water absorption performance of the high-titanium heavy slag micro-powder can be effectively improved, and the working performance, the mechanical property, the durability and the like of the obtained concrete can be ensured; and the related preparation method is relatively simple and relatively low in cost, and has remarkable economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to modified high-titanium heavy slag powder and a preparation method thereof. Background Art

[0002] Blast furnace slag is an industrial waste discharged during the smelting of pig iron. It is a silicate material and has great potential application value in the production of ready-mixed concrete. The chemical composition of high-titanium heavy slag is similar to that of ordinary blast furnace slag, mainly CaO, SiO2, Al2O3, MgO, etc., but the TiO2 content is particularly high (up to 20-29%), which is a typical high-titanium slag, making it very different from ordinary slag in performance.

[0003] High-titanium heavy slag aggregates and powders have been used in concrete to a certain extent, but there are still many problems that have not been solved: (1) Compared with general blast furnace slag, the TiO2 content of high-titanium heavy slag powder is greater than 20%, and the active ingredient content is lower; (2) High-titanium heavy slag powder is porous and the TiO2 particles contained in it have a high specific surface area and water absorption, which can easily absorb moisture in concrete and increase the viscosity of concrete, resulting in a large amount of admixtures and poor working performance; (3) TiO2 and other components are difficult to disperse evenly in concrete, which may introduce micropores or voids, reduce the density and durability of concrete, and lead to poor performance in terms of freeze-thaw cycle resistance and permeability resistance. Summary of the invention

[0004] The main purpose of the present invention is to provide a modified high-titanium heavy slag powder for concrete, improve the activity and water absorption of the high-titanium heavy slag powder, and ensure the working performance, mechanical properties and durability of the obtained concrete.

[0005] To achieve the above solution, the technical solution adopted by the present invention is:

[0006] A modified high-titanium heavy slag powder, whose raw materials include high-titanium heavy slag waste and a composite activation modification additive. The components in the composite activation modification additive and their weight proportions include: 15-20 parts of dispersant, 35-40 parts of water, 30-35 parts of n-propanol, 6-10 parts of sodium methoxide, 0.5-2 parts of 1,2-bis(triethoxysilyl)ethane, and 7-12 parts of isobutyltriethoxysilane.

[0007] In the above scheme, the dosage of the composite activation modifier is 0.05-0.2% of the weight of the high-titanium heavy slag waste.

[0008] In the above scheme, the particle size of the high-titanium heavy slag waste is 0 to 5 mm.

[0009] In the above scheme, the main chemical components and their mass percentages in the high-titanium heavy slag waste include: TiO2 20-29%, CaO 23-46%, SiO2 20-35%, Al2O3 9-15%, and MgO 2-10%.

[0010] In the above scheme, the dispersant is one or more of diethanol monoisopropanolamine, sodium alkylbenzene sulfonate, polyethylene glycol, triethanolamine, polyvinyl pyrrolidone and the like.

[0011] Preferably, the dispersant comprises sodium alkylbenzene sulfonate and triethanolamine.

[0012] Furthermore, the mass ratio of the sodium alkylbenzene sulfonate to triethanolamine is 1:0.8-1.2.

[0013] The above-mentioned method for preparing modified high-titanium heavy slag powder comprises the following steps:

[0014] 1) Firstly, sodium methoxide and n-propanol are mixed, and then water, a dispersant, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane are added in sequence, and mixed evenly to obtain a composite activated modifier;

[0015] 2) Grinding the high-titanium heavy slag waste and the composite activation modifier to obtain the modified high-titanium heavy slag powder.

[0016] In the above scheme, the grinding step uses a grinding equipment which can be selected from a ball mill, a vertical mill or a high-pressure roller mill. The grinding time of different equipment is determined according to the 45μm sieve residue of the powder, and the minimum grinding time when the 45μm sieve residue of the powder is <10% is taken.

[0017] The modified high-titanium heavy slag powder prepared according to the above scheme has a 45μm sieve residue of less than 10%.

[0018] The principle of the present invention is:

[0019] (1) The present invention uses high-titanium heavy slag waste as the main raw material, combined with a composite activation modifier and a grinding process, which can effectively reduce the water absorption rate of high-titanium heavy slag powder and enhance its gelling activity in concrete.

[0020] (2) In the composite activation modifier, sodium methoxide is hydrolyzed to produce methoxyl groups (CH3O -) can increase the nucleophilicity of silanol after hydrolysis and catalyze the modification reaction; sodium methoxide reacts with silicates and metal ions in high-titanium heavy slag powder to increase the -OH group, which provides more binding sites for the subsequent hydrophobic modification reaction; at the same time, sodium methoxide is strongly alkaline in aqueous solution, and during the grinding process, it can change the crystal structure of low gelling active components in high-titanium heavy slag powder and reduce its crystallinity, thereby increasing the gelling activity of high-titanium heavy slag powder; in addition, sodium methoxide also removes impurities such as insoluble salts or organic matter on the surface of the particles, and improves the smoothness of the surface of high-titanium heavy slag powder.

[0021] (3) The triethoxysilyl groups in isobutyltriethoxysilane and 1,2-bis(triethoxysilyl)ethane generate active silanol (Si-OH) after hydrolysis, which can undergo condensation reaction with the binding sites on the surface of high-titanium heavy slag powder under the catalysis of sodium methoxide to form a strong Si-O-Si covalent bond, so that the hydrophobic groups are distributed on the surface of the powder, thereby reducing the water absorption rate of the high-titanium heavy slag powder; compared with 1,2-bis(triethoxysilyl)ethane, the hydrophobic effect of the isobutyl group in isobutyltriethoxysilane is stronger, but the two silane groups in 1,2-bis(triethoxysilyl)ethane can promote the uniformity and efficiency of the reaction and form a denser cross-linked structure. After the two are combined, the modification efficiency and stability can be effectively guaranteed.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. When the modified high-titanium heavy slag powder of the present invention is used as a concrete admixture, it can effectively improve the adverse effects of high-titanium heavy slag on the working performance and durability of concrete;

[0024] 2. The modified high-titanium heavy slag micropowder of the present invention greatly improves the water absorption rate and gelling activity of the micropowder through the combined action of grinding and composite activation modifier, thereby increasing the utilization value of the high-titanium heavy slag micropowder and promoting its recycling;

[0025] 3. The preparation method involved in the present invention is relatively simple and low in cost, and can achieve high added value utilization of high-titanium heavy slag waste, and is suitable for promotion and application. DETAILED DESCRIPTION

[0026] The applicant will further explain the present invention in detail below in conjunction with specific embodiments so that those skilled in the art can more clearly understand the present invention. However, the following content should not be construed as limiting the scope of protection of the claims of the present invention.

[0027] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

[0028] In the following examples, the high-titanium heavy slag waste used was provided by Panzhihua Iron and Steel, and its main chemical components and their mass percentages include: TiO2 22%, CaO 26%, SiO2 24%, Al2O3 14%, MgO 6%; the particle size is 0-5mm; the density is 1858kg / m 3 , the fine powder content is 9.6wt%.

[0029] Example 1

[0030] A modified high-titanium heavy slag micropowder, the raw materials of which are composed of high-titanium heavy slag waste and activation modification additives; wherein the amount of the composite activation modifier is 0.1% of the weight of the high-titanium heavy slag waste, and the composite activation modifier comprises the following raw materials in parts by weight: 15 parts of dispersant, 35 parts of water, 35 parts of n-propanol, 6 parts of sodium methoxide, 1 part of 1,2-bis(triethoxysilyl)ethane, and 8 parts of isobutyltriethoxysilane; wherein the dispersant is a compound of sodium alkylbenzene sulfonate and triethanolamine in a mass ratio of 1:1;

[0031] The preparation method of the modified high-titanium heavy slag powder is:

[0032] 1) Mix the weighed dispersant, water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, and stir evenly to obtain a composite activated modifier;

[0033] 2) Put high-titanium heavy slag waste and composite activation modifier into the ball mill successively, and grind for 15 minutes until the 45μm sieve residue is less than 10%;

[0034] 3) Discharge the powder to obtain modified high-titanium heavy slag powder for concrete.

[0035] Example 2

[0036] A modified high-titanium heavy slag micropowder, the raw materials of which are composed of high-titanium heavy slag waste and activation modification additives; wherein the amount of the composite activation modifier is 0.1% of the weight of the high-titanium heavy slag waste, and the composite activation modifier comprises the following raw materials in parts by weight: 17 parts of dispersant, 36 parts of water, 30 parts of n-propanol, 9 parts of sodium methoxide, 1 part of 1,2-bis(triethoxysilyl)ethane, and 7 parts of isobutyltriethoxysilane; wherein the dispersant is a compound of sodium alkylbenzene sulfonate and triethanolamine in a mass ratio of 1:1;

[0037] The preparation method of the modified high-titanium heavy slag powder is:

[0038] 1) Mix the weighed dispersant, water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, and stir evenly to obtain a composite activated modifier;

[0039] 2) Put high-titanium heavy slag waste and composite activation modifier into the ball mill successively, and grind for 15 minutes until the 45μm sieve residue is less than 10%;

[0040] 3) Discharge the powder to obtain modified high-titanium heavy slag powder for concrete.

[0041] Example 3

[0042] A modified high-titanium heavy slag micropowder, the raw materials of which are composed of high-titanium heavy slag waste and activation modification additives; wherein the amount of the composite activation modifier is 0.1% of the weight of the high-titanium heavy slag waste, and the composite activation modifier comprises the following raw materials in parts by weight: 15 parts of dispersant, 35 parts of water, 30 parts of n-propanol, 6 parts of sodium methoxide, 2 parts of 1,2-bis(triethoxysilyl)ethane, and 12 parts of isobutyltriethoxysilane; wherein the dispersant is a composite of sodium alkylbenzene sulfonate and triethanolamine in a mass ratio of 1:1;

[0043] The preparation method of the modified high-titanium heavy slag powder is:

[0044] 1) Mix the weighed dispersant, water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, and stir evenly to obtain a composite activated modifier;

[0045] 2) Put high-titanium heavy slag waste and composite activation modifier into the ball mill successively, and grind for 15 minutes until the 45μm sieve residue is less than 10%;

[0046] 3) Discharge the powder to obtain modified high-titanium heavy slag powder for concrete.

[0047] Example 4

[0048] A modified high-titanium heavy slag micropowder, the raw materials of which are composed of high-titanium heavy slag waste and activation modification additives; wherein the amount of the composite activation modifier is 0.1% of the weight of the high-titanium heavy slag waste, and the composite activation modifier comprises the following raw materials in parts by weight: 20 parts of dispersant, 35 parts of water, 31 parts of n-propanol, 6 parts of sodium methoxide, 1 part of 1,2-bis(triethoxysilyl)ethane, and 7 parts of isobutyltriethoxysilane; wherein the dispersant is a compound of sodium alkylbenzene sulfonate and triethanolamine in a mass ratio of 1:1;

[0049] The preparation method of the modified high-titanium heavy slag powder is:

[0050] 1) Mix the weighed dispersant, water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, and stir evenly to obtain a composite activated modifier;

[0051] 2) Put high-titanium heavy slag waste and composite activation modifier into the ball mill successively, and grind for 15 minutes until the 45μm sieve residue is less than 10%;

[0052] 3) Discharge the powder to obtain modified high-titanium heavy slag powder for concrete.

[0053] Example 5

[0054] A modified high-titanium heavy slag micropowder, the raw materials of which are composed of high-titanium heavy slag waste and activation modification additives; wherein the amount of the composite activation modifier is 0.1% of the weight of the high-titanium heavy slag waste, and the composite activation modifier comprises the following raw materials in parts by weight: 20 parts of dispersant, 35 parts of water, 31 parts of n-propanol, 6 parts of sodium methoxide, 1 part of 1,2-bis(triethoxysilyl)ethane, and 7 parts of isobutyltriethoxysilane; wherein the dispersant is a compound of sodium alkylbenzene sulfonate and triethanolamine in a mass ratio of 1:1;

[0055] The preparation method of the modified high-titanium heavy slag powder is:

[0056] 1) Mix the weighed dispersant, water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, and stir evenly to obtain a composite activated modifier;

[0057] 2) Put high-titanium heavy slag waste and composite activation modifier into the ball mill successively, and grind for 10 minutes until the 45μm sieve residue is less than 10%;

[0058] 3) Discharge the powder to obtain modified high-titanium heavy slag powder for concrete.

[0059] Example 6

[0060] A modified high-titanium heavy slag micropowder, the raw materials of which are composed of high-titanium heavy slag waste and activation modification additives; wherein the amount of the composite activation modifier is 0.2% of the weight of the high-titanium heavy slag waste, and the composite activation modifier comprises the following raw materials in parts by weight: 20 parts of dispersant, 35 parts of water, 31 parts of n-propanol, 6 parts of sodium methoxide, 1 part of 1,2-bis(triethoxysilyl)ethane, and 7 parts of isobutyltriethoxysilane; wherein the dispersant is a compound of sodium alkylbenzene sulfonate and triethanolamine in a mass ratio of 1:1;

[0061] The preparation method of the modified high-titanium heavy slag powder is:

[0062] 1) Mix the weighed dispersant, water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, and stir evenly to obtain a composite activated modifier;

[0063] 2) Put high-titanium heavy slag waste and composite activation modifier into the ball mill successively, and grind for 10 minutes until the 45μm sieve residue is less than 10%;

[0064] 3) Discharge the powder to obtain modified high-titanium heavy slag powder for concrete.

[0065] Comparative Example 1

[0066] A high-titanium heavy slag powder, the preparation method of which comprises the following steps:

[0067] 1) Mix the weighed dispersant (sodium alkylbenzene sulfonate and triethanolamine in a mass ratio of 1:1), water, n-propanol, sodium methoxide, 1,2-bis(triethoxysilyl)ethane, and isobutyltriethoxysilane, and stir evenly to obtain a composite activated modifier;

[0068] 2) Put the high-titanium heavy slag waste and 0.05% of the weight of the dispersant into a ball mill and grind for 10 minutes, discharge the powder, and obtain high-titanium heavy slag powder for concrete.

[0069] Comparative Example 2

[0070] A modified high-titanium heavy slag powder, whose preparation method is roughly the same as that of Example 1, except that: the composite activation modifier does not contain sodium methoxide, and the composite activation modifier comprises the following raw materials in parts by weight: 15 parts of dispersant, 35 parts of water, 30 parts of n-propanol, 12 parts of sodium methoxide, 1 part of 1,2-bis(triethoxysilyl)ethane, and 7 parts of isobutyltriethoxysilane.

[0071] Comparative Example 3

[0072] A modified high-titanium heavy slag powder, whose preparation method is roughly the same as that of Example 1, except that: the composite activation modifier includes the following raw materials in parts by weight: 15 parts of dispersant, 35 parts of water, 30 parts of n-propanol, 12 parts of sodium methoxide, 1 part of 1,2-bis(triethoxysilyl)ethane, and 7 parts of isobutyltriethoxysilane.

[0073] Comparative Example 4

[0074] A modified high-titanium heavy slag powder, whose preparation method is roughly the same as that of Example 1, except that: the composite activation modifier does not contain 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane; the composite activation modifier comprises the following raw materials in parts by weight: 20 parts of dispersant, 44 parts of water, 30 parts of n-propanol, and 6 parts of sodium methoxide.

[0075] Comparative Example 5

[0076] A modified high-titanium heavy slag powder, whose preparation method is roughly the same as that of Example 1, except that: the composite activation modifier includes the following raw materials in parts by weight: 15 parts of dispersant, 30 parts of water, 30 parts of n-propanol, 6 parts of sodium methoxide, 3 parts of 1,2-bis(triethoxysilyl)ethane, and 16 parts of isobutyltriethoxysilane.

[0077] Comparative Example 6

[0078] A modified high-titanium heavy slag powder, whose preparation method is roughly the same as that of Example 1, except that: the composite activation modifier does not contain 1,2-bis(triethoxysilyl)ethane; the composite activation modifier comprises the following raw materials in parts by weight: 15 parts of dispersant, 35 parts of water, 30 parts of n-propanol, 6 parts of sodium methoxide, and 14 parts of isobutyltriethoxysilane.

[0079] According to the methods described in the examples and comparative examples, modified high-titanium heavy slag powder was prepared for concrete testing. While ensuring the consistency of concrete working performance, the dosage of admixtures and concrete compressive strength were compared. The concrete test mix ratio is shown in Table 1, where the cement grade used is P·O 42.5, the fly ash is Class I fly ash, and the machine-made sand is Lafarge stone silt sand. The test was carried out according to GB / T 50080-2016 "Standard for Test Methods of Ordinary Concrete Mixtures Performance" and GBT 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", and the test results are shown in Table 2.

[0080] Table 1 Concrete test mix ratio (kg / m 3 )

[0081] cement Fly ash Modified high titanium heavy slag powder Machine-made sand gravel water Benchmarks 260 60 / 960 980 160 Examples and Comparative Examples 230 30 60 960 980 160

[0082] Table 2 Test results

[0083]

[0084] It can be seen from the test data that the concrete working performance of Examples 1 to 6 is good, the water consumption and the amount of admixture are close to those of the benchmark group, and after the modified high-titanium heavy slag powder in the example mix ratio replaces cement and fly ash at a ratio of 1:1, the concrete strength does not change much, indicating that the modified high-titanium heavy slag powder prepared by the present invention has good activity.

[0085] In Comparative Example 1, only high-titanium heavy slag waste was ground without using a modifier. The water consumption and admixture dosage in the concrete test were both high, and the initial working performance was good, but the loss was fast. In addition, the unmodified high-titanium heavy slag powder had poor activity, and the 7d and 28d strengths of the concrete were both relatively low.

[0086] Comparative Example 2 did not use sodium methoxide, and the amount of admixture was slightly higher than that of the benchmark group, but the 7d and 28d strengths were still low and did not meet the C30 concrete strength requirements.

[0087] Comparative Example 3 used excessive sodium methylate, and the initial working performance of the concrete was good, but the loss was fast. The 7d strength of the concrete was good, but the 28d strength growth was small, which did not meet the strength requirements of C30 concrete.

[0088] Comparative Example 4 did not use 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, the water consumption and admixture dosage of the concrete were both high, the strength was low, and the strength requirement of C30 concrete was not met.

[0089] Comparative Example 5 used excessive amounts of 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane, resulting in reduced water consumption, poor water retention of concrete, and severe water seepage.

[0090] Comparative Example 6 did not use 1,2-bis(triethoxysilyl)ethane, the high-titanium heavy slag powder had poor hydrophobic stability, the concrete had a good initial working condition, the loss was fast, and the concrete strength was also low.

[0091] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A modified high-titanium heavy slag powder, characterized in that: The raw materials include high-titanium heavy slag waste and an activated modification additive. The components in the composite activated modification additive and their weight proportions include: 15 to 20 parts of dispersant, 35 to 40 parts of water, 30 to 35 parts of n-propanol, 6 to 10 parts of sodium methoxide, 0.5 to 2 parts of 1,2-bis(triethoxysilyl)ethane, and 7 to 12 parts of isobutyltriethoxysilane.

2. The modified high-titanium heavy slag powder according to claim 1, characterized in that: The usage of the composite activation modifier is 0.05-0.2% of the weight of the high-titanium heavy slag waste.

3. The modified high-titanium heavy slag powder according to claim 1, characterized in that: The particle size of the high-titanium heavy slag waste is 0 to 5 mm.

4. The modified high-titanium heavy slag powder according to claim 1, characterized in that: The high-titanium heavy slag waste has a bulk density of 1820-1880 kg / m 3 , the fine powder content is 6 to 12 wt%.

5. The modified high-titanium heavy slag powder according to claim 1, characterized in that: The main chemical components and their mass percentages in the high-titanium heavy slag waste include: TiO2 20-29%, CaO 23-46%, SiO2 20-35%, Al2O39-15%, and MgO 2-10%.

6. The modified high-titanium heavy slag powder according to claim 1, characterized in that: The dispersant is one or more of diethanol monoisopropanolamine, sodium alkylbenzene sulfonate, polyethylene glycol, triethanolamine, and polyvinyl pyrrolidone.

7. The modified high-titanium heavy slag powder according to claim 1, characterized in that: The dispersant includes sodium alkylbenzene sulfonate and triethanolamine.

8. The modified high-titanium heavy slag powder according to claim 1, characterized in that: The mass ratio of the sodium alkylbenzene sulfonate to triethanolamine is 1:0.8-1.

2.

9. The method for preparing the modified high-titanium heavy slag powder according to any one of claims 1 to 8, characterized in that: The steps include: 1) Firstly, sodium methoxide and n-propanol are mixed, and then water, a dispersant, 1,2-bis(triethoxysilyl)ethane and isobutyltriethoxysilane are added in sequence, and mixed evenly to obtain a composite activated modifier; 2) Grinding the high-titanium heavy slag waste and the composite activation modifier to obtain the modified high-titanium heavy slag powder.

10. The preparation method according to claim 9, characterized in that: The 45 μm sieve residue of the modified high-titanium heavy slag powder is less than 10%.

Citation Information

Cited By

  • Method for producing special anti-abrasion agent for hydraulic concrete by using high-titanium heavy slag

    CN120229901A

  • A multi-element composite admixture and a production process thereof

    CN122541132A